Italian bank crisis: Flexible application of BRRD rules, or a bailout in disguise? - Jan Famfollet; Eliška Sankotová (Review of Economic Perspectives, 2020)
The economic and financial crisis of the year 2008 highlighted the need for banking sector regulation via the creation of the banking union. The Bank Recovery and Resolution Directive (BRRD) represents an important milestone in the formation of the banking union. It is supposed inter alia to replace the existing practice of bailing out failing banks by the opposite principle of bail-in, which makes the bank recapitalized from the internal resources at the detriment of investors and creditors. However, the Italian solution of handling its failing banks took advantage of existing loopholes in the new regulatory system. Eventually, it went against the spirit of the new rules by deploying taxpayers' money to deal with the banks' failure. This article evaluates the Italian approach and contemplates the adequacy of the new rules-based system by comparing its potentially beneficial room for flexibility with alleged malfunction and unreliability. Finally, it discusses the potential impact of the Italian approach on the further process of completing the banking union, in particular the establishment of its last pillar, the common deposit guarantee scheme.
Keywords: G18; G33; G38; 330; banking union; banking supervision; BRRD; bail-in; bailout; precautionary recapitalisation; non-performing loans; Italian banking sector